Differences in prefrontal cortex activation and deactivation during strategic episodic verbal memory encoding in mild cognitive impairment - Balardin, Joana B.; Batistuzzo, Marcelo; Moraes Martin, Maria da Graça; Sato, Joao; Smid, Jerusa; Porto, Claudia; Savage, Cary R.; Nitrini, Ricardo; Amaro Jr, Edson; Miotto, Eliane C. (Frontiers in Aging Neuroscience, 2015)
In this study we examined differences in fMRI activation and deactivation patterns during episodic verbal memory encoding between individuals with MCI (n=18) and healthy controls (n=17). Participants were scanned in two different sessions during the application of self-initiated or directed instructions to apply semantic strategies at encoding of word lists. MCI participants showed reduced free recall scores when using self-initiated encoding strategies that were increased to baseline controls’ level after directed instructions were provided. During directed strategic encoding, greater recruitment of frontoparietal regions was observed in both MCI and control groups; group differences between sessions were observed in the ventromedial prefrontal cortex and the right superior frontal gyrus. This study provides evidence suggesting that differences of activity in these regions may be related to encoding deficits in MCI, possibly mediating executive functions during task performance.